Diaspora of Venezuelan talents: Characteristics of a highly-qualified migration (Gestión y Gerencia, 2021)
Articles are presented on the characteristics of the current Venezuelan diaspora of highly qualified talents. The results of a survey show the characteristics and personal capacities of Venezuelan professionals in the diaspora. Successful emigrant professionals narrate their experiences to adapt to new conditions of life and professional activity in other countries. Contains the book presented, knowledge that can be used to learn about the problem of the migration of Venezuelan talents in the receiving countries and appreciate their capabilities. It is an important contribution to the theories and experiences on qualified migration.
Keywords: Migration; Venezuelan diaspora; technological capabilities; qualified migration; science and technology in Venezuela